1990
DOI: 10.1111/j.1365-2796.1990.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma lipoproteins in acute malaria

Abstract: Plasma lipid and lipoprotein concentrations were monitored in 16 patients with acute malaria. Plasma high density lipoprotein (HDL) levels decreased dramatically during the first 3 d after diagnosis to around 0.2 mmol l-1 (reference range 0.8-1.6 mmol l-1). The low HDL levels were related to parasitaemia, and rapidly recovered after successful therapy. Plasma triglyceride concentrations were moderately increased and plasma low density lipoprotein (LDL) cholesterol concentrations decreased during the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…A number of studies have reported an altered lipid composition in lipoproteins from patients with P. falciparum infections (3,21,44,45,59). However, the extent and nature of the changes differ between different studies, and it is difficult to predict the effects of these changes on the efficiency of presentation of PfEMP1 in infected RBCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported an altered lipid composition in lipoproteins from patients with P. falciparum infections (3,21,44,45,59). However, the extent and nature of the changes differ between different studies, and it is difficult to predict the effects of these changes on the efficiency of presentation of PfEMP1 in infected RBCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical Method Concentrations of CXM in plasma were determined by a modified high pressure liquid chromatography method (HPLC) previously described by Nilsson-Ehle I, 12) which modifies the ratio of the mobile phase consisting of acetic acid/water/methanol (1 : 69 : 30 by vol). To 0.5 ml of plasma, 1 ml of dimethylformamide was added and then the mixture stirred rapidly on a vortex-type mixer before being heated for 1 min in a water bath set at 60°C.…”
Section: )mentioning
confidence: 99%
“…This finding is in contrast to data reported in other studies that showed elevated levels of lipoproteins in patients suffering from malaria infection. [37][38][39][40] On the contrary, a study reported that hyperlipidemia is one of the indicators of malaria infection; the hypothesis for the changes is basically due to increased VLDL production and increased mobilization of free fatty acids from adipose tissue in response to stress. 41 However, the evidence of higher concentrations of serum lipids in the infected group might be due to adipose tissue lipolysis, impairment in lipoprotein lipase system, increases in de novo hepatic fatty acid synthesis, and suppression of fatty acid oxidation in severe infection.…”
mentioning
confidence: 99%